PEMERIKSAAN DAN PENYULUHAN KESEHATAN (DESA SUKARSA KECAMATAN SALAWU KABUPATEN TASIKMALAYA) - Andhika Lungguh Perceka; Wahyudin; Hasbi Taobah Ramdani; Desy Syswianti; Susan Susyanti (LP4M STIKes Karsa Husada Garut, 2020)
Health checks and counseling to residents of Sukarasa Village, Salawu Tasikmalaya have goals and targets for lecturers to instill a sense of empathy and increase a sense of help among fellow believers. Along with increasing the incidence of various chronic diseases, this activity is carried out for screening/detecting chronic diseases and degenerative diseases as the age of local residents increases. With this health check, it is hoped that residents can find out whether the individual is suffering from a degenerative disease or not, and can improve preventive measures. In addition to health checks, community service activities also include free treatment aimed at people who are sick, both infectious and non-infectious diseases. The purpose of this activity is to treat sick residents with curative therapy and can slightly reduce the cost of patient treatment. The methodology of this activity is through health education and free health checks to villagers. From a number of 70 patients who were treated in Sukarasa Village, 37 men and 43 women were found, of which 25 had cholesterol, 15 had uric acid, 10 had sugar and 20 were normal/healthy.